A consultoria colaborativa como estratégia na formação continuada de professores sobre o AEE à pessoa com surdocegueira - Santos, Nágib José Mendes dos (2014)
When thinking about Special Needs Care (SNC) directed to the person with deafblindness inside the context of inclusive school, especially when it concerns the congenital deafblindness, it is, for many, considered a major challenge. That occurs due to the need of a training that can provide the construction of specific knowledge to help these students develop ways to communicate and interact with their enviroment. This study consists of a qualitative research that aimed to investigate the collaborative consultation as a mean of continued education offered to the teachers who worked with Special Needs Care (SNC) at the public school of the city of Arapiraca/Alagoas. Specifically, the objectives of this essay were: 1. Analyze the prior knowledge of the participants on the SNC directed the student with deafblindness; 2. Analyze the (re)concepts, starting from the collaborative consultation, concerning the theme of specialized educational services to the deafblind student; and 3. Speculate on the results of the Collaborative Consulting, as a mean of continuing education for the SNC to be offered to people with deafblindness in the city of Arapiraca/AL. With that purpose, data was collected through poll, focus groups and semi-structured interview. The resulting data from the aforementioned methods were analyzed from the perspective of thematic analysis described by Minayo (1996) and Bardin (1979). The results showed that before the collaborative consultation, the knowledge about the theme of deafblindness was considered incipient by some of the participants, among the teachers involved in the research, only two (02) have never heard of deafblindness. It was also discovered that the thoughts of participants on deafblindness in the early collaborative consultation, were reduced to the idea of ​​an individual fully deprived of the senses of sight and hearing and, therefore, knew the world and communicated only by the sense of tact. In terms of training, the participants showed a need for further articulation of theory and practice. About the school inclusion of the deafblind person, it was considered possible. However, with a need to face the existence of certain aspects considered relevant by the participants of the study: like the involvement and the training of the teacher from the regular classes; participation from the entire school in promoting the inclusion of deafblind person; the participation of the family and, finally, the support of skilled professionals. We conclude that, despite the difficulties surrounding the theme of special needs educational to people with deafblindness, the collaborative consultation can be considered as a viable strategy for training teacheers on the subject of SNC and deafblindness.